Age Is Relative—Impact of Donor Age on Induced Pluripotent Stem Cell-Derived Cell Functionality - Strässler, Elisabeth Tamara; Aalto-Setälä, Katriina; Kiamehr, Mostafa; Landmesser, Ulf; Kränkel, Nicolle (Frontiers in Cardiovascular Medicine, 2018)
Induced pluripotent stem cells (iPSCs) avoid many of the restrictions that hamper the application of human embryonic stem cells: limited availability of source material due to legal restrictions in some countries, immunogenic rejection and ethical concerns. Also, the donor’s clinical phenotype is often known when working with iPSCs. Therefore, iPSCs seem ideal to tackle the two biggest tasks of regenerative medicine: degenerative diseases with genetic cause (e.g. Duchenne's muscular dystrophy) and organ replacement in age-related diseases (e.g. end-stage heart or renal failure), especially in combination with recently developed gene-editing tools. In the setting of autologous transplantation in elderly patients, donor age becomes a potentially relevant factor which needs to be assessed. Here, we review and critically discuss available data pertinent to the questions: How does donor age influence the reprogramming process and iPSC cell functionality? Would it even be possible to reprogram senescent somatic cells? How does donor age affect iPSC differentiation into specialised cells and their functionality? We also identify research needs, which might help resolve current unknowns. Until recently, most hallmarks of ageing were attributed to an accumulation of DNA damage over time, and it was thus expected that DNA damage from a somatic cell would accumulate in iPSCs and the cells derived from them. In line with this, a decreased lifespan of cloned organisms compared to the donor was also observed in early cloning experiments. Therefore, it was questioned for a time whether iPSC derived from an old individual’s somatic cells would suffer from early senescence and thus, may not be a viable option either for disease modelling nor future clinical applications. Instead, typical signs of cellular ageing are reverted in the process of iPSC reprogramming, and iPSCs from older donors do not show diminished differentiation potential, nor do iPSC-derived cells from older donors suffer early senescence or show functional impairments when compared to those from younger donors. Thus, the data would suggest that donor age does not limit iPSC application for modelling genetic diseases nor regenerative therapies. However, open questions remain, e.g. regarding the potential tumourigenicity of iPSC-derived cells and the impact of epigenetic pattern retention.